Do rice farmers have knowledge of greenhouse gas (GHG) emission mitigation strategies? New evidence from Nigeria - Sander, Björn Ole; Ali, Jauhar; Romasanta, Ryan Rogelio; Murugaiyan, Varunseelan; Khatibi, Seyed Mahdi; Noel, Okonkwo Kenechi; Chikaodi, Chukwurah Veronica; Uchenna Theresa, Osuji; Ndidi, Akande Stella; Chimeriri, Anyanwu Daniel; Success, Esiobu Nnaemeka (Sciencedomain International, 2023)
In Nigeria, rice remains a major staple food source for the rapidly growing population of an estimated 210 million people. However, traditional rice production carried out in flooded soil is associated with greenhouse gas (GHG) emissions, mainly anthropogenic methane (CH4) and nitrous oxide (N2O) in Nigeria. Both CH4 and N2O are harmful GHGs that raise the temperature of the planet by retaining heat in the atmosphere. Reduction of GHG emissions is critical, and understanding farmers' knowledge of GHG emission mitigation strategies would be crucial to reducing emissions from rice fields and producing rice in a cleaner environment. Incidentally, there is a dearth of empirical evidence in the current debate. The absence of this study creates a gap in research and makes it extremely pertinent that the study be systematically undertaken. Our study described the socio-economic characteristics of the rice farmers and ascertained their knowledge level on GHG mitigation strategies. We utilized questionnaire and focused group discussion (FGD) as the primary methods of data collection. Descriptive statistics and mean score analysis were used to analyze the data collected. On average, we found that the rice farmers were 45 years old. Most (72%) were male. Only 31% of the farmers had contacted extension agents and were visited twice per calendar year. We found that among various GHG emission mitigation strategies identified in the area, the farmers had significant knowledge of the use of Aerobic Rice Varieties (ARV) (x̄ = 3.61; σ = 0.87) but low knowledge of the use of Alternate Wetting and Drying (AWD) (x̄ = 1.88; σ = 0.45). Our findings confirmed the incidence of GHG emissions in rice fields and that farmers have started practicing GHG mitigation strategies to reduce emissions from rice in the area. However, among various constraints, our study observed that inadequate technical know-how is negatively challenging rice farmers’ capacity to implement and scale-up GHG emissions mitigation strategies. Therefore, our study recommends that the government should strengthen and support agricultural extension service systems to enable them to visit farmers’ farms regularly to transmit and build farmers capacity in the use of recent GHG emission mitigation strategies and innovations in rice fields.